CO2 hydrate formation enhancement via bare and hybrid silica nanoparticles effect: Implications for hydrate-based CO2 sequestration - Al-Anssari, Sarmad; Sadeq, Dhifaf; Hassan, Hassanain A.; Al-Taie, Ahmed Hamid; Arian, Zain-Ul-Abedin (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Carbon dioxide geological storage gives tremendous promise for mitigating anthropogenic carbon emissions. CO2 hydrate has been given rising attention due to its potential in carbon geo-sequestration projects. The effect of silica nanoparticles (SiNPs) on the kinetics of CO2 hydrate formation was systematically studied at 3.5 MPa and 280 K. Pure (bare) and surface-modified (hybrid) SiNPs were separately characterized and used in this study. The effect of bare and hybrid SiNPs concentrations on the induction time of CO2 hydrate formation was investigated. A high-pressure, high-temperature stainless steel vessel was used as a hydrate reactor, and pressure-temperature data were continuously recorded to follow the hydrate formation process. Results revealed that the SiNPs significantly impact the kinetics of CO2 hydrate formation. The increase of Hybrid SiNPs concentration (>0.03 wt% hybrid SiNPs), significantly reduces the induction time and thus accelerates the rapid formation of CO2 hydrate. In contrast, bare SiNPs showed a lower effect on CO2 hydrate formation. Further, the increase of bare SiNPs (e.g., >0.07 wt% bare SiNPs) can tend to eliminate the effect of NPs on induction time. Thus, surface-modified SINPs can significantly enhance CO2 hydrate formation when formulated correctly.